Development of Culture-Based Interactive Comic Media to Improve Mathematical Literacy in Primary Schools - Regita Ajeng Pramesti; Wahyudi Wahyudi (SAINTIS Publishing, 2025)
This study aims to develop a culture-based interactive comic medium as an innovative tool to enhance mathematical literacy among primary school students. The research employed a Research and Development (RD) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The analysis phase was conducted through observations and teacher interviews to identify appropriate media needs. The media was developed in the form of a comic incorporating local cultural contexts from Salatiga and material on whole number operations. Product validation was conducted by three experts, yielding results of 96% (media), 100% (content), and 100% (instructional design), all indicating a “highly valid” category. Effectiveness testing was carried out using pretests and posttests, showing an increase in the average score from 31.10% to 65.50%. Practicality testing showed results of 92% from students and 97% from teachers, both categorized as “highly practical.” The results demonstrate that the culture-based interactive comic media is effective and feasible for improving mathematical literacy among primary school students.